Implementasi Pendekatan TPACK dalam Mendukung Transformasi Digital Guru PAI-BP di SMK N 1 Bawang Kabupaten Banjarnegara - Sofyan Ade Irawan; Ulpah Maspupah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Digital transformation in education requires teachers to effectively integrate technology, pedagogy, and subject content in the learning process. One framework that supports this integration is Technological Pedagogical and Content Knowledge (TPACK). SMK N 1 Bawang, Banjarnegara Regency, has implemented various digital technologies in Islamic Religious Education and Character Building (PAI-BP) learning. However, the implementation of TPACK and its contribution to teachers’ digital transformation require further investigation. This study aims to describe the implementation of TPACK in PAI-BP learning and analyze its role in supporting teachers’ digital transformation. This research employed a qualitative approach with a field research design. The participants consisted of three PAI-BP teachers, one principal, and six students. Data were collected through observation, interviews, and documentation. Data validity was ensured through source triangulation and technique triangulation, while data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that TPACK implementation has been carried out effectively through the integration of technology, pedagogy, and content knowledge. Teachers utilized various digital media, including PowerPoint, Canva, Google Classroom, Google Forms, Quizizz, YouTube, and TikTok, combined with Problem-Based Learning (PBL), Project-Based Learning (PjBL), discussions, and presentations. The implementation of TPACK supports teachers’ digital transformation by enhancing digital competence and developing more interactive, student-centered learning practices. Keywords: Digital Transformation, Educational Technology, PAI-BP Learning, Teachers, TPACK